Ureaplasma urealyticum infection presenting as altered mental status in a post-chemotherapy patient: Case report and literature review - Kok, Eunice J. Y.; Lee, Y. L. (Frontiers in Medicine, 2022)
Hyperammonemia due to Ureaplasma infection is rare but often fatal, largely due to the delayed recognition, diagnosis and treatment of the condition. It has mostly been described in solid organ transplant patients in the literature. This case presents the diagnostic challenge of an immunocompromised patient with previous resected pancreatic head adenocarcinoma and chemotherapy, presenting with altered mental status due to hyperammonemia from Ureaplasma infection. It is imperative to consider this condition in unexplained hyperammonemia, especially in immunocompromised patients. Timely diagnosis of this condition can help to reduce complications from encephalopathy such as cerebral edema and seizures.